Upaya Peningkatan Perekonomian Masyarakat Melalui Budidaya Ikan Koi di Desa Kemloko Kecamatan Nglegok Kabupaten, Blitar - Rusda, Moh Ulimta; Sari, Citra Mulya (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTPoverty is a social problem that is global in nature, and is a problem that is often faced by many people in Indonesia. To overcome this problem, the people in Kemloko Village, Nglegok District, Blitar are doing koi fish farming to improve their economy. This study aims to analyze the increase in the economy in Kemloko village and the factors that influence the income of koi fish farming entrepreneurs. This study uses a qualitative descriptive approach using primary data, the methods used are observation and interviews. The analysis technique used goes through three stages, namely sorting out important or main things and focusing on important things in the field, then presenting the data in order to better understand the case being researched. The conclusions from this study (1) Koi fish farming activities carried out by the Kelud Koi Koi Fish Cultivation group can improve the economic level of the Kemloko village community for the better. In addition, this activity can increase the productivity of the community. (2) Land area, seeds and feed are factors that influence the level of koi fish production in Kemloko village. (3) Capital and market competition are obstacles that are often faced by the Kemloko village community when carrying out koi fish farming activities.Keywords: Economic improvement, Community economy, Productivity, Poverty